PENGARUH KETERSEDIAAN KOLEKSI TERHADAP PEMANFAATAN KOLEKSI DI UPT. PERPUSTAKAAN UNIVERSITAS UDAYANA - Dewi S, Yenni Rahmawati; Haryant, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT The purpose of this research is to know the influence of collection availability against collection utilization in UPT. Udayana University Library. This type of research is quantitative descriptive. The research is located at UPT. Udayana University Library. The population of this study was 37.696 and a sample number of 100 people was calculated using the slovin formula. The sampling of this study uses the Accidental Sampling technique. This study uses data collection techniques in the form of questionnaires, observations, and library studies. The data analysis technique used in this study is a simple linear regression analysis. The study gained result that there were significant influences from the availability of collection to the utilization of the collection. Keywords: College Library, Collection Availability, Collection Utilization.